Profile of Psoriasis Vulgaris Patients Treated with Methotrexate at Dr. Soetomo Hospital, Surabaya, 2017–2018 - Damayanti Damayanti; Karina Dyahtantri Pratiwi; Wisnu Triadi Nugroho (Universitas Airlangga, 2021)
Background: Psoriasis Vulgaris is a chronic inflammatory skin disease that affects patients’ quality of life. Methotrexate is the first-line and most effective systemic therapy in psoriasis vulgaris management. Purpose: The aim of this study was to evaluate clinical improvement after methotrexate therapy and any adverse effects of methotrexate therapy in psoriasis vulgaris management. Methods: The data for this descriptive, retrospective study were retrieved from the medical records of 22 psoriasis vulgaris patients who were treated with methotrexate therapy between January 2017 and June 2018 in the Child Kemuning Ward (IRNA), Dr. Soetomo General Hospital in Surabaya, East Java. Results: Data for a total of 22 subjects were collected for this study. The majority of the subjects were in the age group 25–59, and the average age was 40.50±17.20. Good clinical improvement (decrease in the body surface area of the lesion) was found in all patients. The adverse effects of methotrexate were evaluated based on the elevation of liver and renal function test levels. An elevation of aspartate aminotransferase levels was found in 11 patients, and an elevation in alanine aminotransferase levels was found in 13 patients. Elevated blood urea nitrogen levels were found in eight patients, and elevated serum creatinine levels were found in four patients. Conclusion: Methotrexate is an effective treatment for severe psoriasis vulgaris management when administered with careful selection and regular monitoring of patients. Application of methotrexate therapy in accordance with the guidelines remains suitable for psoriasis vulgaris management with vigilance regarding methotrexate’s adverse effects.